Sequential Decision Making and Information Aggregation in Small Networks*. Issue 2 (7th April 2014) - Patty, John W.; Penn, Elizabeth Maggie
<x content-type="archive" xml:space="preserve">Abstract</x> This article describes and investigates a model of strategic sequential decision making in networked policy-making environments with three agents. The primary interest is the effect of network structure on sequential policy making and information aggregation. The model and results illustrate how individual policy decisions of varying weight (in terms of a decision maker's unilateral effect on policy outcomes) can enable information aggregation in decentralized environments. In the studied environment, the incentive compatibility conditions for information aggregation are not invariant to network isomorphisms: individuals' positions in the network matter. The study derives exact conditions for every acyclic network of three or fewer agents and illustrates the counterintuitive nature of comparative statics with respect to both network structure and individual agents' policy preferences and discretionary authority.